DEVELOPMENT OF A NUMBERED HEAD TOGETHER (NHT) LEARNING MODEL IN SENIOR HIGH SCHOOL 1 SUWAWA IN HISTORY SUBJECT - Pakaya, Tri Novita; Yunus, Resmiyati; Mondong, Tonny Iskandar (Satmata: Journal of Historical Education Studies, 2024)
The learning process is an interaction between educators and students as well as the teaching materials used. The learning process is a communication process between students and teachers. The aim of this research is to improve student learning outcomes through the Numbered Head Together (NHT) learning model in history subjects at SMA Negeri 1 Suwawa. The research method used is the classroom action research method. With procedures starting from the preparation stage, action implementation, monitoring and evaluation stage, analysis and reflection stage, data collection techniques, where the data collection itself is by means of observation and documentation. The results of the research show that the application of the Numbered Head Together (NHT) learning model can improve the learning outcomes in history subjects for students in class Numbered Head Together (NHT) students' learning motivation has increased. Because in the first cycle the predetermined target was achieved, namely 86.2%, the desired target of this research has been achieved. My suggestion as a researcher for the learning methods used by SMA Negeri 1 Suwawa is not only to focus on using the lecture method, but also to try other teaching methods such as Numbered Head Together (NHT), as well as other teaching methods.